2018
DOI: 10.14203/oldi.2018.v3i2.161
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Characteristic and Abrasion Hazard in Putri Island, Nongsa, Batam

Abstract: Putri Island, Nongsa is the outer and frontier island of NKRI region bordering Singapore. Its existence is very important both economically and politically. The management of  Putri Island should consider the coastal characteristic that describes character and physical of the beach as the result of interaction between marine influence and coastal condition, geophysical and anthropogenic elements. The purposes of the study are mapping the coastal characteristics as an effort to manage frontier island and descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…The characteristics of sediments formed in this facies are thought to have a coarse grain size. If correlated with previous studies, this facies is comparable to Conglomerate Various Material (Hernawan et al, 2018) as a part of Tanjungkerotang Formation (Tmpt) (Kusnama, 1994).…”
Section: Interpretation Of Gpr Radar Unitsupporting
confidence: 89%
See 4 more Smart Citations
“…The characteristics of sediments formed in this facies are thought to have a coarse grain size. If correlated with previous studies, this facies is comparable to Conglomerate Various Material (Hernawan et al, 2018) as a part of Tanjungkerotang Formation (Tmpt) (Kusnama, 1994).…”
Section: Interpretation Of Gpr Radar Unitsupporting
confidence: 89%
“…However, based on the results of the P3GL investigation (2005) showed that during the Pleistocene -Holocene (Quaternary), Putri Islands are composed of reef limestone and coarse to fine fragments of sediment. This indicates that during this Quaternary time there were evolution of depositional environment from fluviatil into marine (Hernawan et al, 2018).…”
Section: Interpretation Of Gpr Radar Unitmentioning
confidence: 75%
See 3 more Smart Citations